Indoor air pollution (PM2.5) due to secondhand smoke in selected hospitality and entertainment venues of Karachi, Pakistan. Issue 5 (15th June 2011) - Nafees, Asaad Ahmed; Taj, Tahir; Kadir, Muhammad Masood; Fatmi, Zafar; Lee, Kiyoung; Sathiakumar, Nalini
Abstract : Objective: To determine particulate matter smaller than 2.5 μm (PM2.5 ) levels at various hospitality and entertainment venues of Karachi, Pakistan. Methods: This was a descriptive cross-sectional study conducted at various locations in Karachi, during July 2009. Sampling was performed at 20 enclosed public places, including hospitality (restaurants and cafés) and entertainment (snooker/billiard clubs and gaming zones) venues. PM2.5 levels were measured using an aerosol monitor. Results: All entertainment venues had higher indoor PM2.5 levels as compared to the immediate outdoors. The indoor PM2.5 levels ranged from 25 to 390 μg/m 3 and the outdoor PM2.5 levels ranged from 18 to 96 μg/m 3 . The overall mean indoor PM2.5 level was 138.8 μg/m 3 (±112.8). Among the four types of venues, the highest mean indoor PM2.5 level was reported from snooker/billiard clubs: 264.7 μg/m 3 (±85.4) and the lowest from restaurants: 66.4 μg/m 3 (±57.6) while the indoor/outdoor ratio ranged from 0.97 to 10.2, highest being at the snooker/billiard clubs. The smoking density ranged from 0.21 to 0.57, highest being at gaming zones. The indoor PM2.5 concentration and smoking density were not significantly correlated (Spearman's correlation coefficient=0.113; p=0.636). Conclusions: This study demonstrates unacceptably high levels of PM2.5 exposure associated with secondhand smoke (SHS) at various entertainment venues of Karachi even after 8 years since the promulgation of smoke-free ordinance (2002) in Pakistan; however, better compliance may be evident at hospitality venues. The results of this study call for effective implementation and enforcement of smoke-free environment at public places in the country.